EFFECT OF SILICIC ACID ON BORON LEACHING IN PLYWOOD MANUFACTURE (Applied Biological Research, 2023)
Boric acid is a well-known wood preservative and fire retardant having  low mammalian toxicity. Its efficacy is affected as it is non-fixed type, water  leachable and effective only in interior conditions. In present study the  effect of silicic acid and treatment methods on permanency of boron in  plywood was studied through leaching test. The plywood was treated with  glue line treatment as well as veneer treatment method with boric acid and  three combinations of boric acid and silicic acid (1:1, 2:1 and 3:1) at 2, 3  and 4% concentrations.With a view to explore the possibility of fixation of  boric acid in combination with silicic acid, the treated samples were  subjected to leaching and then boron content was analyzed in leached  samples. The results showed that boron was easily leached from the  samples treated with boric acid only; whereas the treatment with the  combination of silicic acid improved boron fixation in samples. The results  of two different treatment methods showed suitability of veneer treatment  to achieve sufficient boron retention in plywood. However, the leaching of  boron was also high in veneer treatment than glue line treatment method.
Keywords: Boric acid; leachability; plywood; silicic acid